2022
DOI: 10.1093/ijnp/pyac041
|View full text |Cite
|
Sign up to set email alerts
|

5-HT5A Receptor Antagonist ASP5736 Ameliorates Several Abnormal Behaviors in an Fmr1-Targeted Transgenic Male Rat Model of Fragile X Syndrome

Abstract: Background Fragile X syndrome (FXS) is a genetic condition that causes a range of developmental problems including intellectual disability, aggressive behavior, anxiety, abnormal sensory processing and cognitive impairment. Despite intensive preclinical research in Fmr1-targeted transgenic mice, an effective treatment for FXS has yet to be developed. We previously demonstrated that ASP5736, a 5-HT5A receptor antagonist, ameliorated scopolamine-induced working memory deficits in mice, referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Noteworthy, both WT and KO rats demonstrated reduced levels of motor activity due to the longer exposure and subsequent familiarity with the open-field apparatus. In agreement with our results, increased motor activity as deduced by the total time spent in the open-field apparatus was observed for Fmr1 KO compared to WT rats [ 38 , 39 ]. Another study [ 40 ] reported that KO rats were hyperactive, only during the first recording interval.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Noteworthy, both WT and KO rats demonstrated reduced levels of motor activity due to the longer exposure and subsequent familiarity with the open-field apparatus. In agreement with our results, increased motor activity as deduced by the total time spent in the open-field apparatus was observed for Fmr1 KO compared to WT rats [ 38 , 39 ]. Another study [ 40 ] reported that KO rats were hyperactive, only during the first recording interval.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding recognition learning and memory, our results agree with other studies showing deficits in the novel object recognition test [ 39 , 45 47 ] and the novel location recognition task [ 48 ], however, one study did not report impairments in recognition and spatial memory [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, investigating possible DA-independent mechanisms that may drive hyperactivity in Fmr1-Δ exon 8 rats also remains an intriguing point that deserves further investigation. For instance, the pharmacological targeting of serotonin 89,90 , GABA 91,92 , BDNF 93,94 , acetylcholine 95 pathways (to mention a few) has been demonstrated to ameliorate abnormal locomotor behaviors in Fmr1-KO mice. Despite dopaminergic aberrations have been extensively documented in Fmr1-KO mice 63,[96][97][98][99] , preclinical data on the striatal DAT activity remain controversial, with some studies reporting a decreased striatal DAT expression 97 , whereas others (including the present results) showing no change in DAT function 99 .…”
Section: Discussionmentioning
confidence: 99%